Gender Equality Observatory for Latin America and the Caribbean. Annual report 2013-2014. Confronting violence against women in Latin America and the Caribbean - Agencia Española de Cooperación Internacional para el Desarrollo (CEPAL, 2015)
The efforts States in our region have made to eradicate violence against women have seen substantial headway on a number of fronts over the past 20 years. This calls for a look at how individual governments have responded and the wide variety of strategies followed. In this report, the Economic Commission for Latin America and the Caribbean (ECLAC) follows up on the Gender Equality Observatory for Latin America and the Caribbean commitment to analyse violence against women. It has been drafted by the Observatory’s participating agencies and organizations: the Pan American Health Organization (PAHO), the United Nations Entity for Gender Equality and the Empowerment of Women (UN-Women); the United Nations Population Fund (UNFPA), the Ibero-American Secretariat (SEGIB) and the Spanish Agency for International Development Cooperation (AECID). The focus is on the situation across the region, progress in meeting international recommendations, national public policies, and constraints and challenges.